Tax Policies of Low Carbon in China: Effectiveness Evaluation, System Design and Prospects - Feng, Ping; Lu, Hongyuan; Li, Wei; Wang, Xinyu (Frontiers in Environmental Science, 2022)
Fiscal and taxation policy tools play an important role in promoting green and low-carbon development. Based on classical tax theory, including the Potter hypothesis and the environmental Kuznets curve, this paper explores the impact of environmental tax regulation on economic growth and carbon emission reduction. We find that resource tax reform could promote green total factor productivity; however, the ad valorem reform of resource tax does not significantly raise the level of low carbon development. This effect varies among different regions as well as different tax cuts and fee reductions. Fiscal revenue decentralization has a reverse adjustment effect on the impact of resource taxes on green total factor productivity. We conclude that it is necessary to deepen the reform of the fiscal and taxation system to achieve the carbon neutrality and emission peak goal.